Basic Issues Of Power Alienation In Vietnam Today (International Journal of Environmental Sciences, 2025)
Alienation of power is a negative phenomenon that occurs when power is misused and deviates from the purpose of serving the common interest, causing many bad consequences for the development of society. From a philosophical perspective, alienation of power is not only an administrative or legal issue but also an issue of ethics, philosophy of life, and the nature of power in society. Studying alienation of power through a philosophical lens supports us clearly in understanding the underlying causes, manifestations, and proposing appropriate solutions to ensure that power is always used correctly, transparently, and responsibly. The article analyzes and clarifies the basic issues related to the alienation of power in Vietnam today. Accordingly, in the current period, the manifestations of power alienation are diverse, mainly expressed through: alienation of power in the performance of public duties and corruption, bribery, profiteering from policies; lack of transparency, low responsibility in accountability; formation of interest groups to manipulate policies and personnel. The article also presents and analyzes three basic solutions to prevent the alienation of power in Vietnam today. The limitation of the article is that it has not pointed out and explored the factors affecting the alienation of power in Vietnam today.